A polysulfone-ZrO2 composite diaphragm, preparation method and application
By adding a sheet of hydrophilic inorganic substances to the polysulfone-ZrO2 composite separator, the efficient dispersion of ZrO2 particles and the improvement of mechanical properties is achieved, and the brittleness of the separator under high temperature and high alkali conditions is solved, and the high hydrophilicity is achieved and excellent mechanical properties.
Patent Information
- Application Number
- CN202210860029.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-21
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2042-07-21
AI Technical Summary
In the existing alkaline electrolytic hydrogen production technology, the alkali resistance stability and mechanical properties of the membrane are insufficient, resulting in the membrane being easily brittle and the hydroxide conductivity when used under high temperature and high alkali conditions.
Polysulfone-ZrO2 composite separator is used, and the ZrO2 particles are efficiently dispersed by interspersing each other by adding sheets of hydrophilic inorganic substances such as graphene, graphene oxide, etc., thereby inhibiting agglomeration and improving mechanical properties and hydrophilicity.
The prepared polysulfone-ZrO2 composite separator has excellent mechanical properties and high hydrophilicity, tensile strength can reach 50-80MPa, elongation at break of 6-15%, and it shows excellent performance in alkaline electrolytic device. Initial performance and durability stability.
Smart Images

Figure CN115287702B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a polysulfone-ZrO2 composite diaphragm, a preparation method and application thereof, and belongs to the field of alkaline water electrolysis diaphragm materials. Background Art
[0002] At present, human society is still highly dependent on fossil energy, and the global energy crisis is imminent. The development of renewable and clean energy is an important development direction. Hydrogen, as a form of energy storage with high energy density and sustainable development, is an ideal energy carrier. Hydrogen production by water electrolysis has the characteristics of zero carbon emissions and high efficiency, and has the potential for large-scale expansion. Among them, alkaline water electrolysis hydrogen production technology has the most mature development, with the advantages of simple tank structure, safety and reliability, and low price. The main reason for the poor performance of traditional alkaline water electrolysis is the high resistance loss caused by the diaphragm and electrolyte. Therefore, the development of high-performance diaphragms is very important for alkaline water electrolysis.
[0003] In recent years, anion exchange membrane (AEM) has been used to replace traditional asbestos cloth or PPS cloth for the process of electrolysis of water to produce hydrogen, which can effectively block the mixing of hydrogen and oxygen and has excellent hydroxide conductivity, but AEM still faces the technical problem of stability in alkaline environment (Energy & Environmental Science, 2012, 5 (7): 7869). In addition, PBI-type ion solvent membrane has excellent gas barrier properties due to its dense structure and is widely used in alkaline electrolysis of water, but it is necessary to achieve a high level of hydroxide conduction function under high alkali concentration. At the same time, long-term stability studies have shown that when it is used under high temperature and high alkali conditions, hydroxide attacks the C2 position of the benzimidazole group, causing the PBI skeleton structure to degrade, so the alkali stability of the ion solvent membrane still needs to be further improved (Energy Environ. Sci., 2019, 12, 3313-3318). At present, most industrial alkaline water electrolyzers still use porous composite diaphragms with good alkali resistance and stability. It is usually composed of a chemically inert polymer base and a hydrophilic inorganic filler. Studies have found that polysulfone has strong hardness, high corrosion resistance and high glass transition temperature, but poor hydrophilicity, and its performance is poor when directly applied to alkaline electrolyzed water. The researchers further improved the hydrophilicity by adding inorganic ZrO2, and the prepared polysulfone-ZrO2 composite diaphragm has good performance in alkaline electrolyzed water (International Journal of Energy Research, 2020, 44 (3): 1875-1885). However, when too much ZrO2 is added, the hydrophilicity of the diaphragm is enhanced, the membrane surface resistance is low, and the hydroxide conductivity is improved, but because ZrO2 nanoparticles are difficult to disperse evenly, they are prone to agglomeration, which makes the diaphragm brittle and the mechanical stability is reduced. Wu et al. synthesized a highly crystalline ZrO2 nanoparticle by solvothermal reaction. These non-aqueous synthesized ZrO2 nanoparticles were highly dispersed in organic media with the help of ligands, but the synthesis steps were relatively complicated (J Mater Sci, 2009, 44: 1613–1621). Hu et al. used cationic surfactant hexadecyltrimethylammonium bromide for self-assembly and formed highly dispersed, nearly spherical, uniform-sized zirconium oxide nanocrystals under hydrothermal conditions. However, there was no bonding between the surfactant and zirconium oxide, only encapsulation induction, resulting in low dispersion efficiency (Journal of the Chinese Ceramic Society, 2006, 34(2): 162-165). Therefore, it is still a challenge to develop simple, efficient, well-dispersed, highly hydrophilic and mechanically stable porous membranes. Summary of the invention
[0004] The purpose of the present invention is to provide a polysulfone-ZrO2 composite diaphragm, a preparation method and an application thereof. The polysulfone-ZrO2 composite diaphragm is a polysulfone-ZrO2 composite diaphragm with good dispersion, strong hydrophilicity and excellent mechanical properties. The application is the application of the polysulfone-ZrO2 composite diaphragm in an alkaline water electrolyzer.
[0005] The polysulfone-ZrO2 composite diaphragm of the present invention is a composite porous diaphragm.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A polysulfone-ZrO2 composite membrane, comprising an organic component polysulfone, an inorganic component ZrO2, and one or more lamellae hydrophilic inorganic substances; wherein x represents the mass of the organic component polysulfone; y represents the mass of the inorganic component ZrO2; z represents the mass of the one or more lamellae hydrophilic inorganic substances, wherein x / (x+y+z) is 0.05-0.45, (y+z) / (x+y+z) is 0.65-0.95, and z / y is 0.01-1, preferably z / y is 0.05-0.3;
[0008] The lamellar hydrophilic inorganic material is selected from one or more of graphene, graphene oxide, boron nitride (BN), molybdenum oxide (MoO3), molybdenum disulfide (MoS2) and layered double metal hydroxides; preferably, the low-valent metal ion in the layered double metal hydroxides (LDHs) is Mg 2+ 、Ni 2+ , Fe 2+ 、Co 2+ and Mn 2+ In one of the above, the high-valent metal ion in the layered double hydroxide (LDHs) is Al 3+ , Fe 3+ and Ti 4+ One of them.
[0009] The present invention proposes a method for preparing a polysulfone-ZrO2 composite diaphragm by adding a lamellar hydrophilic inorganic substance. The lamellar hydrophilic inorganic substance and the spherical ZrO2 particles are interpenetrated to achieve efficient dispersion, inhibiting large-area agglomeration of nano-sized ZrO2 particles and making their distribution uniform, thereby improving the mechanical properties of the diaphragm without sacrificing hydrophilicity, and the operation is simple and efficient. The structural composition of the prepared polysulfone-ZrO2 composite diaphragm can be represented by x, y, and z, wherein x represents the mass of several components of polysulfone; y represents the mass of the inorganic component ZrO2; and z represents the mass of one or more lamellar inorganic substances. Its structural composition is characterized in that: x / (x+y+z) is an arbitrary number between 0.05-0.45, (y+z) / (x+y+z) is an arbitrary number between 0.65-0.95 (if x / (x+y+z) is lower than 0.05, the composite film formed is brittle and has poor flexibility and cannot be used normally; if x / (x+y+z) is higher than 0.45, the composite film has poor hydrophilicity and low hydroxyl conduction level). Meanwhile, z / y is an arbitrary number between 0.01-1, preferably an arbitrary number between 0.05-0.3.
[0010] Furthermore, x / (x+y+z) is 0.05 to 0.45. For example, x / (x+y+z) is 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40 or 0.45.
[0011] Furthermore, (y+z) / (x+y+z) is 0.65 to 0.95. (y+z) / (x+y+z) is 0.65, 0.70, 0.75, 0.80, 0.85, 0.90 or 0.95.
[0012] Further, z / y is 0.01 to 1. For example, z / y is 0.01, 0.05, 0.10, 0.20, 0.30, 0.40, 0.50, 0.60, 0.70, 0.80, 0.90 or 1. Preferably, z / y is 0.05, 0.10, 0.20 or 0.3.
[0013] A method for preparing a polysulfone-ZrO2 composite membrane as described in any one of the above items comprises the following steps:
[0014] (1) At room temperature, ZrO2 and one or more lamellar hydrophilic inorganic substances are first dispersed in an organic solvent to obtain a mixed solution, the mixed solution is further ground and dispersed for 0.5-2 hours, and then stirred and dispersed at 80-120° C. for 0.5-4 hours, and then polysulfone is added in batches and stirred for 6-10 hours, and the solid content of the final casting solution is controlled at 50-70wt%;
[0015] (2) Next, the obtained casting solution is coated on a glass plate by knife coating, pre-evaporated at room temperature for 5-300 seconds, and then immersed in one or more mixed non-solvents at -25-30°C for 5-30 minutes for conversion, condensation, film formation and washing to remove the solvent, thereby achieving phase inversion;
[0016] (3) Soaking the membrane obtained in the above step in deionized water at 50-100° C. for 24-48 hours to remove the residual solvent in the membrane, and finally preparing a polysulfone-ZrO2 composite membrane. Preferably, the composite membrane has a pore size of 0.10-150 nm, a porosity of 1-200% and a thickness of 80-500 μm.
[0017] According to the preparation method of the polysulfone-ZrO2 composite membrane, the organic solvent described in step (1) is N-methylpyrrolidone (NMP), dimethylacetamide (DMAc), N,N'-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), tetramethyl urea (TMU) and the like.
[0018] According to the preparation method of the polysulfone-ZrO2 composite membrane, the non-solvent described in step (2) is: one or a mixed solvent of two or more selected from water, methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, tert-butanol, etc.
[0019] The use of the polysulfone-ZrO2 composite diaphragm as described in any one of the above or the polysulfone-ZrO2 composite diaphragm prepared by the method as described in any one of the above in an alkaline water electrolysis device comprises the following steps:
[0020] (1) Preparation of membrane electrode assembly for water electrolysis device
[0021] Pure nickel mesh foam is used for both cathode and anode. The pure nickel mesh foam is placed in a hot press and hot-pressed at 80-120°C for 0.5-10 minutes before being taken out and compressed to a thickness of 150-200 μm. Then, the polysulfone-ZrO2 composite diaphragm is sandwiched between two nickel mesh foam electrodes to obtain a membrane electrode assembly with an effective area of 4 cm 2 .
[0022] (2) Assemble the water electrolysis device by sandwiching the membrane electrode assembly between the cathode and the anode
[0023] Electrochemical tests were performed in the presence of anodic and cathodic electrolytes. Polarization curves were obtained by measuring the cell voltage at different current densities in 1-10 M electrolytes at 20-100 °C, and at 20-100 °C, 50-500 mA cm -2 The durability is evaluated under constant temperature and constant current.
[0024] According to the application of the polysulfone-ZrO2 composite diaphragm in an alkaline water electrolysis device, the electrolyte in the alkaline water electrolysis device is one or more of potassium hydroxide, potassium carbonate, potassium bicarbonate, sodium hydroxide, sodium carbonate and sodium bicarbonate.
[0025] The beneficial results of the present invention are:
[0026] (1) The present invention proposes a method for efficiently preparing a polysulfone-ZrO2 composite membrane by adding flaky inorganic substances, which is simple and efficient to operate.
[0027] (2) The prepared polysulfone-ZrO2 composite membrane has good dispersibility, less inorganic particle agglomeration, uniform distribution, excellent mechanical properties, tensile strength of up to 50-80MPa, and elongation at break of up to 6-15%;
[0028] (3) The prepared composite porous membrane has a relatively uniform pore size and distribution, low membrane surface resistance, and strong gas barrier properties;
[0029] (4) The polysulfone-ZrO2 composite membrane is used in alkaline electrolytic cells and has excellent initial performance and durable stability >500h (60℃, 200mA / cm 2 ). BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a SEM image of the polysulfone-ZrO2 composite membrane prepared in Example 1;
[0031] Figure 2 Polarization curves of the polysulfone-ZrO2 composite membranes prepared in Examples 3, 5, 8, 13 and the comparative example in an alkaline water electrolysis device. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is described in detail below through specific embodiments, but it should be clearly stated that these embodiments are for illustration and are not to be construed as limiting the scope of the present invention.
[0033] Some of the raw materials used in the following examples of the present invention come from:
[0034] Polysulfone (Sigma-Aldrich, 428302, M w =50000-500000)
[0035] ZrO2 (Sigma-Aldrich, 230693, particle size 20-2000nm)
[0036] Example 1
[0037] (1) At room temperature, 80 g ZrO2 and 5 g graphene oxide (Sigma-Aldrich, 796034) (z / y=0.0625, z refers to the mass of graphene oxide, y refers to the mass of ZrO2) were first dispersed in N,N'-dimethylformamide (DMF), and the mixed solution was further ground and dispersed by a ball mill for 0.5 h, and then stirred at 120 ° C for 2 h, and then 15 g polysulfone was added in batches and stirred at high speed for 4 h. Finally, the solid content of the casting solution was controlled at 60 wt%.
[0038] (2) Next, the obtained casting solution was coated on a clean glass plate, pre-evaporated at room temperature for 10 seconds, and then slowly immersed in isopropanol at 0°C for 10 minutes for conversion, condensation, film formation and washing to remove the solvent, thereby achieving phase inversion.
[0039] (3) The membrane obtained in the above steps was immersed in deionized water at 80°C for 24 h to fully remove the residual solvent in the membrane. The polysulfone-ZrO2 composite porous membrane was finally prepared. The membrane thickness was 150 μm, and it had excellent mechanical properties (elastic modulus of 1054.23 MPa; elongation at break was 7.25%; tensile strength was 54.91 MPa), and the membrane surface resistance was 0.28 mΩ×cm 2 And through SEM, it was found that ZrO2 was well dispersed and no large-scale agglomeration occurred.
[0040] The steps for applying the prepared polysulfone-ZrO2 composite porous diaphragm in an alkaline water electrolysis device are as follows:
[0041] (1) Preparation of membrane electrode assembly for water electrolysis device. Pure nickel mesh foam (Suzhou Shengerno Technology, thickness 500 μm) was selected for both anode and cathode. The pure nickel mesh foam (2 cm × 2 cm) was placed in a hot press and hot-pressed at 80°C for 5 minutes. After that, it was taken out and compressed to a thickness of 170 μm. Then, the prepared polysulfone-ZrO2 composite porous diaphragm was sandwiched between two nickel mesh foam electrodes to obtain a membrane electrode assembly with an effective area of 4 cm 2 .
[0042] (2) The membrane electrode assembly is sandwiched between the cathode and the anode to assemble the water electrolysis device. The electrochemical test is carried out while immersed in the anode and cathode electrolytes. Under the conditions of 6M KOH and 80°C, its initial performance can reach 500mA·cm -2 -1.87V, and at 80℃, 200mA·cm -2 The durability was evaluated under a constant current of .
[0043] Example 2
[0044] At room temperature, 75 g ZrO2 and 10 g graphene oxide (Sigma-Aldrich, 796034) (z / y=0.1333, z refers to the mass of graphene oxide, y refers to the mass of ZrO2) were first dispersed in N,N'-dimethylformamide (DMF), the mixed solution was further ground and dispersed by a ball mill for 0.5 h, then stirred at 120°C for 2 h, and then 15 g polysulfone was added in batches for high-speed stirring for 4 h, and the solid content of the final casting solution was controlled at 60 wt%. The remaining experimental steps and application steps were the same as in Example 1, and the obtained composite diaphragm had a thickness of 150 μm.
[0045] Example 3
[0046] At room temperature, 70 g ZrO2 and 15 g graphene oxide (Sigma-Aldrich, 796034) (z / y=0.2143, z refers to the mass of graphene oxide, y refers to the mass of ZrO2) were first dispersed in N,N'-dimethylformamide (DMF), the mixed solution was further ground and dispersed by a ball mill for 0.5 h, then stirred at 120°C for 2 h, and then 15 g polysulfone was added in batches for high-speed stirring for 4 h, and the solid content of the final casting solution was controlled at 60 wt%. The remaining experimental steps and application steps were the same as in Example 1, and the obtained composite diaphragm had a thickness of 120 μm.
[0047] Example 4
[0048] At room temperature, 70 g ZrO2 and 15 g graphene oxide (Sigma-Aldrich, 796034) (z / y=0.2143, z refers to the mass of graphene oxide, y refers to the mass of ZrO2) were first dispersed in N,N'-dimethylformamide (DMF), the mixed solution was further ground and dispersed by a ball mill for 1 h, and then stirred at 120°C for 3 h, and then 15 g polysulfone was added in batches for high-speed stirring for 4 h, and the solid content of the final casting solution was controlled at 60 wt%. The remaining experimental steps and application steps were the same as in Example 1, and the obtained composite diaphragm had a thickness of 150 μm.
[0049] Example 5
[0050] At room temperature, 70 g ZrO2 and 15 g boron nitride (Sigma-Aldrich, 255475) (z / y=0.2143, z refers to the mass of boron nitride, y refers to the mass of ZrO2) were first dispersed in N,N'-dimethylformamide (DMF), the mixed solution was further ground and dispersed by a ball mill for 1 hour, and then stirred at 120°C for 3 hours, and then 15 g polysulfone was added in batches for high-speed stirring for 4 hours, and the solid content of the final casting solution was controlled at 60 wt%. The remaining experimental steps and application steps were the same as in Example 1, and the obtained composite diaphragm had a thickness of 200 μm.
[0051] Example 6
[0052] At room temperature, 70 g ZrO2 and 15 g boron nitride (Sigma-Aldrich, 255475) (z / y=0.2143, z refers to the mass of boron nitride, y refers to the mass of ZrO2) were first dispersed in N,N'-dimethylformamide (DMF), the mixed solution was further ground and dispersed by a ball mill for 1 hour, and then stirred at 120°C for 3 hours, and then 15 g polysulfone was added in batches for high-speed stirring for 4 hours, and the solid content of the final casting solution was controlled at 70 wt%. The remaining experimental steps and application steps were the same as in Example 1, and the obtained composite diaphragm had a thickness of 180 μm.
[0053] Example 7
[0054] At room temperature, 80 g of ZrO2 and 10 g of boron nitride (Sigma-Aldrich, 255475) (z / y=0.125, z refers to the mass of boron nitride, y refers to the mass of ZrO2) were first dispersed in N,N'-dimethylformamide (DMF), and the mixed solution was further ground and dispersed by a ball mill for 1 hour, then stirred at 120°C for 3 hours, and then 10 g of polysulfone was added in batches and stirred at high speed for 6 hours. The resulting composite diaphragm had a thickness of 200 μm.
[0055] Example 8
[0056] At room temperature, 80 g ZrO2, 5 g boron nitride (Sigma-Aldrich, 255475) and 5 g graphene (Sigma-Aldrich, 900412) (z / y=0.125, z refers to the sum of the mass of boron nitride and graphene, y refers to the mass of ZrO2) were first dispersed in N,N'-dimethylformamide (DMF), the mixed solution was further ground and dispersed by a ball mill for 1 h, and then stirred at 120°C for 3 h, and then 10 g polysulfone was added in batches for high-speed stirring for 6 h, and the solid content of the final casting solution was controlled at 75 wt%. The remaining experimental steps and application steps were the same as in Example 1, and the obtained composite diaphragm had a thickness of 220 μm.
[0057] Example 9
[0058] At room temperature, 60 g ZrO2 and 25 g MoS2 (Sigma-Aldrich, 804169) (z / y=0.4166, z refers to the mass of MoS2, y refers to the mass of ZrO2) were first dispersed in N,N'-dimethylformamide (DMF), the mixed solution was further ground and dispersed by a ball mill for 2 h, and then stirred at 120°C for 4 h, and then 15 g polysulfone was added in batches for high-speed stirring for 6 h, and the solid content of the final casting solution was controlled at 60 wt%. The remaining experimental steps and application steps were the same as in Example 1, and the obtained composite diaphragm had a thickness of 160 μm.
[0059] Example 10
[0060] At room temperature, 60 g ZrO2 and 25 g MoS2 (z / y=0.4166) (Sigma-Aldrich, 804169) (z / y=0.4166, z refers to the mass of MoS2, y refers to the mass of ZrO2) were first dispersed in dimethylacetamide (DMAc), the mixed solution was further ground and dispersed by a ball mill for 2 h, and then stirred at 120°C for 4 h, and then 15 g polysulfone was added in batches for high-speed stirring for 6 h, and the solid content of the final casting solution was controlled at 60 wt%. The remaining experimental steps and application steps were the same as in Example 1, and the obtained composite diaphragm had a thickness of 200 μm.
[0061] Embodiment 11
[0062] The same as Example 1, except that in the specific step (2) of preparing the polysulfone-ZrO2 composite membrane: the obtained casting solution is scraped on a clean glass plate, pre-evaporated at room temperature for 60 seconds, and then slowly immersed in methanol at -5°C for 5 minutes for conversion, condensation, film formation and washing to remove the solvent, thereby achieving phase inversion. The remaining experimental steps and application steps are the same as Example 1, and the obtained composite membrane has a thickness of 170 μm.
[0063] Example 12
[0064] The same as Example 1, except that in the specific step (2) of preparing the polysulfone-ZrO2 composite membrane: the obtained casting liquid is scraped on a clean glass plate, pre-evaporated at room temperature for 120 seconds, and then slowly immersed in methanol at -10°C for 15 minutes for conversion, condensation, film formation and washing to remove the solvent, thereby achieving phase inversion. The obtained composite membrane has a thickness of 210 μm.
[0065] Example 13
[0066] The same as Example 9, except that in the specific step (2) of preparing the polysulfone-ZrO2 composite membrane: the obtained casting liquid is scraped on a clean glass plate, pre-evaporated at room temperature for 10 seconds, and then slowly immersed in a mixed solution of ethanol and water (ethanol: water volume ratio = 1:1) at -20°C for 5 minutes for conversion, condensation, film formation and washing to remove the solvent, thereby achieving phase inversion, and the obtained composite membrane has a thickness of 150μm.
[0067] Embodiment 14
[0068] The same as Example 9, except that in the specific step (2) of preparing the polysulfone-ZrO2 composite membrane: the obtained casting liquid is scraped on a clean glass plate, pre-evaporated at room temperature for 30 seconds, and then slowly immersed in a mixed solution of isopropanol and water (isopropanol: water volume ratio = 1:1) at 5°C for 8 minutes for conversion, condensation, film formation and washing to remove the solvent, thereby achieving phase inversion. The obtained composite membrane has a thickness of 160 μm.
[0069] Comparative Example
[0070] In this example, a polysulfone-ZrO2 composite membrane was prepared without adding a lamellar inorganic substance as a comparative example: at room temperature, 85 g of ZrO2 was first dispersed in N,N'-dimethylformamide (DMF), the mixed solution was further ground and dispersed by a ball mill for 0.5 h, and then stirred at 120°C for 2 h, and then 15 g of polysulfone was added in batches and stirred at high speed for 4 h, and the solid content of the final casting solution was controlled at 60 wt%. The remaining experimental steps and application steps were the same as in Example 1, and the obtained composite membrane had a thickness of 250 μm.
[0071] Figure 1 The following are SEM images of the polysulfone-ZrO2 composite membranes prepared in Example 1 and the comparative example. Figure 1 (a) is the SEM image of the upper surface of the comparative composite diaphragm, from which it can be seen that ZrO2 is unevenly dispersed and agglomerated; Figure 1 (b) is a SEM image of the upper surface of the composite membrane of Example 1. It can be seen that ZrO2 and graphene oxide are well dispersed with each other and no large-scale agglomeration occurs.
[0072] Table 1 shows the mechanical properties and membrane surface resistance performance parameters of the polysulfone-ZrO2 composite diaphragms prepared in all embodiments and comparative examples. Specifically, Table 1 shows the mechanical properties comparison of the polysulfone-ZrO2 composite diaphragms prepared in all embodiments and comparative examples; Table 1 shows the membrane surface resistance comparison of the polysulfone-ZrO2 composite diaphragms prepared in all embodiments and comparative examples at 6M KOH and room temperature.
[0073] Table 1
[0074]
[0075]
[0076] From Table 1, it can be found that compared with not adding lamellar inorganic matter, after adding lamellar inorganic matter, the elongation at break and tensile strength of the composite diaphragm are improved to varying degrees, and the membrane surface resistance can also be maintained unchanged or reduced.
[0077] Figure 2 The polarization curves of the polysulfone-ZrO2 composite membranes prepared in Examples 3, 5, 8, 13 and the comparative example in an alkaline water electrolysis device. Figure 2 It can be seen that when using pure nickel foam electrodes, the electrolysis performance of the embodiments is improved to a certain extent compared with the comparative examples, among which the performance of embodiment 8 is the most obvious, and 1.78V can reach 500mA / cm 2 , while the comparative example is at 500mA / cm 2 The lower voltage is up to 2.02V.
[0078] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A polysulfone-ZrO2 composite membrane, characterized in that: The polysulfone-ZrO2 composite membrane comprises an organic component polysulfone, an inorganic component ZrO2, and one or more lamellae hydrophilic inorganic substances; wherein x represents the mass of the organic component polysulfone; y represents the mass of the inorganic component ZrO2; z represents the mass of the one or more lamellae hydrophilic inorganic substances, wherein x / (x+y+z) is 0.05-0.45, (y+z) / (x+y+z) is 0.65-0.95, and z / y is 0.01-1; The lamellar hydrophilic inorganic material is selected from one or more of graphene, graphene oxide, boron nitride, molybdenum oxide, molybdenum disulfide and layered double metal hydroxides; the low-valent metal ion in the layered double metal hydroxide is Mg 2+ 、Ni 2+ , Fe 2+ 、Co 2+ and Mn 2+ One of the above, wherein the high-valent metal ion in the layered double hydroxide is Al 3+ , Fe 3+ and Ti 4+ One of; The preparation method of the polysulfone-ZrO2 composite diaphragm is as follows: (1) At room temperature, ZrO2 and one or more lamellar hydrophilic inorganic substances are first dispersed in an organic solvent to obtain a mixed solution, the mixed solution is further ground and dispersed for 0.5-2 hours, and then stirred and dispersed at 80-120° C. for 0.5-4 hours, and then polysulfone is added in batches and stirred for 6-10 hours, and the solid content of the final casting solution is controlled at 50-70wt%; (2) Next, the obtained casting solution is coated on a glass plate by knife coating, pre-evaporated at room temperature for 5-300 seconds, and then immersed in one or more mixed non-solvents at -25-30°C for 5-30 minutes for conversion, condensation, film formation and washing to remove the solvent, thereby achieving phase inversion; (3) Soaking the membrane obtained in the above step in deionized water at 50-100° C. for 24-48 hours to remove the residual solvent in the membrane, and finally preparing a polysulfone-ZrO2 composite membrane.
2. The composite diaphragm according to claim 1, characterized in that: The lamellar hydrophilic inorganic matter and the granular ZrO2 are interspersed with each other.
3. The method for preparing the polysulfone-ZrO2 composite membrane according to claim 1, characterized in that: The steps include: (1) At room temperature, ZrO2 and one or more lamellar hydrophilic inorganic substances are first dispersed in an organic solvent to obtain a mixed solution, the mixed solution is further ground and dispersed for 0.5-2 hours, and then stirred and dispersed at 80-120° C. for 0.5-4 hours, and then polysulfone is added in batches and stirred for 6-10 hours, and the solid content of the final casting solution is controlled at 50-70wt%; (2) Next, the obtained casting solution is coated on a glass plate by knife coating, pre-evaporated at room temperature for 5-300 seconds, and then immersed in one or more mixed non-solvents at -25-30°C for 5-30 minutes for conversion, condensation, film formation and washing to remove the solvent, thereby achieving phase inversion; (3) soaking the membrane obtained in the above step in deionized water at 50-100° C. for 24-48 hours to remove the residual solvent in the membrane, and finally preparing a polysulfone-ZrO2 composite membrane; The polysulfone-ZrO2 composite membrane has a pore size of 0.10-150 nm, a porosity of 1-200% and a thickness of 80-500 μm.
4. The method according to claim 3, characterized in that: The organic solvent described in step (1) is N-methylpyrrolidone, dimethylacetamide, N,N'-dimethylformamide, dimethyl sulfoxide or tetramethyl urea.
5. The method according to claim 3, characterized in that: The non-solvent described in step (2) is: one or a mixed solvent of two or more of water, methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol and tert-butanol.
6. Use of the polysulfone-ZrO2 composite diaphragm according to any one of claims 1-2 or the polysulfone-ZrO2 composite diaphragm prepared by the method according to any one of claims 3-5 in an alkaline water electrolysis device, characterized in that: The steps include: (1) Preparation of membrane electrode assembly for water electrolysis device Pure nickel mesh foam is used for both cathode and anode. The pure nickel mesh foam is placed in a hot press, hot-pressed at 80-120° C. for 0.5-10 minutes, then taken out and compressed to a thickness of 150-200 μm. Then, the polysulfone-ZrO2 composite diaphragm is sandwiched between two nickel mesh foam electrodes to obtain a membrane electrode assembly. (2) Assemble the water electrolysis device by sandwiching the membrane electrode assembly between the cathode and the anode Electrochemical tests were carried out while immersing the battery in the anode and cathode electrolytes. Polarization curves were obtained by measuring the battery voltage at different current densities in 1-10M electrolyte at 20-100°C, and durability was evaluated at a constant temperature and constant current of 20-100°C, 50-500mA·cm-2.
7. The use according to claim 6, characterized in that: The electrolyte in the alkaline water electrolysis device is one or more of potassium hydroxide, potassium carbonate, potassium bicarbonate, sodium hydroxide, sodium carbonate and sodium bicarbonate.
Citation Information
Patent Citations
Preparation method of highly hydrophilic polysulfone ultrafiltration membrane
CN105664739A
Hydrophilic polysulfone (PSF) / silicon dioxide blended hollow fiber membrane and preparation method thereof
CN107570021A